Identifying the Evolution of Learning Methods in Physical Education: A Systematic Review of Modern Approaches and Digital Integration - Sauqi Sawa Bikalawan; Advendi Kristiyandaru; Muchamad Arif Al Ardha; Nurhasan Nurhasan; Sevesti Violin Wilujeng Herista; Tays Rona Legeayem; Nizam Umarushalih (Physical Education Theory and Methodology)
Background. The learning process in physical education requires an appropriate and effective learning method. It is incumbent upon physical education teachers to determine learning methods that take into account the conditions of their students.